1966
DOI: 10.1103/physrev.144.582
|View full text |Cite
|
Sign up to set email alerts
|

Theory of the Urbach Rule

Abstract: The two-vibrational-mode model proposed by Toyozawa and Mahr to account for the Urbach rule is considered both in the semiclassical approximation and in the full quantum theory. The semiclassical line shape accounts for both the exponential Urbach tail and the central Gaussian region of the absorption band.Quantum modifications make the semiclassical line shape incorrect for an excited state stable to odd-parity lattice distortions. The quantum line shape for an unstable excited state is shown to be qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

1970
1970
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(42 citation statements)
references
References 15 publications
0
42
0
Order By: Relevance
“…(1), has been observed universally in crystals as well as glasses. Extensive research over many decades [2] has shown that it arises from transitions between localized electronic levels resulting from band-edge fluctuations and extended states [3,4]. In a pioneering work on amorphous Si, the fluctuations in the single-particle energies at the band edges obtained from ab initio molecular-dynamics (MD) simulations in the local density approximation were found to be in good agreement with experimentally measured band tail widths [5].…”
mentioning
confidence: 56%
“…(1), has been observed universally in crystals as well as glasses. Extensive research over many decades [2] has shown that it arises from transitions between localized electronic levels resulting from band-edge fluctuations and extended states [3,4]. In a pioneering work on amorphous Si, the fluctuations in the single-particle energies at the band edges obtained from ab initio molecular-dynamics (MD) simulations in the local density approximation were found to be in good agreement with experimentally measured band tail widths [5].…”
mentioning
confidence: 56%
“…2͑a͒. The optical absorption coefficient near the fundamental absorption band has an exponential dependency, which is given by the Urbach's rule as 36,37 It can be seen that when SiO 2 content increases, the band gap energy values increase, occurring at 4.6 and 5.2 eV for the LSCAS and AM39 ͑the glass with higher SiO 2 content͒ samples, respectively.…”
Section: Optical Absorption Coefficient and Band Gap Determinationmentioning
confidence: 98%
“…The second integral in the expression (3) which can be evaluated, say, by the stationary phase method 1191 is much smaller than the first one in the region IQ,v ( < A, and may be neglected.…”
Section: Shape Of the Emission Spectrum Due To Impurity Centresmentioning
confidence: 99%